HUBUNGAN FAKTOR LINGKUNGAN DENGAN KEJADIAN DERMATITIS PADA ANAK USIA SEKOLAH DI DESA TABANG BARAT KECAMATAN RAINIS KABUPATEN KEPULAUAN TALAUD - Lawita, Andrep Jusak; Sarimin, Sisfiani; Karundeng, Michael (Universitas Sam Ratulangi, 2015)
ABSTRACT:Dermatitis is derived from the word derm/o-(skin) and and itis (inflammation),so that dermatitis can be translated as a condition in which the skin is inflamed. Thisresearch purpose is to know whether there is a relationship to environmental factors withdermatitis incident in children of school age in the village of West Tabang, Rainis District ofTalaud Island. The research design is descriptive analytic with a cross sectional approach.Engineering samples of data collection is done by sampling the total number of 35 children.The results of this study using the chi-square test, of 35 respondents (100%) found thatelementary school-age children have a good environment (LBA) with acute dermatitis asmany as 11 respondents (31.4%), and chronic dermatitis as one respondent (2.9 %). Whileelementary school children who have a bad neighborhood (LKB) with acute dermatitis is asmuch as 4 respondents (11.7%) and chronic dermatitis 19 respondents (54.3%). So that thevalue is p = 0.00 smaller than Ã¡ = 0.005. Conclusions from the research that has beenconducted in the village of West tabang Rainis District of Talaud Islands is there arelationship between environmental factors with dermatitis incident in children of school age.Constructive suggestions are expected to be a scientific contribution and information forfurther research on the relationship of environmental factors with dermatitis incident inchildren of school age.Keyword : Dermatitis, Environmental FactorsABSTRAK:Dermatitis berasal dari kata derm/o- (kulit) dan itis (Radang/inflamasi), sehinggadermatitis dapat diterjemahkan sebagai suatu keadaan di mana kulit mengalami inflamasi.Tujuan Penelitian Untuk mengetahui apakah ada hubungan faktor lingkungan dengankejadian dermatitis pada anak usia sekolah di Desa Tabang Barat Kecamatan RainisKabupaten Talaud. Desain Penelitian yang digunakan dalam penelitian ini deskriptif analitikdengan menggunakan pendekatan cross sectional. Sampel Teknik pengambilan datadilakukan dengan total sampling dengan jumlah 35 Anak. Hasil Penelitian denganmenggunakan uji chi-square dari 35 responden (100%) didapatkan,bahwa anak usia sekolahdasar memiliki lingkungan baik (LBA) dengan dermatitis akut sebanyak 11 responden(31,4%), dermatitis kronik sebanyak 1 responden (2,9%). Sedangkan anak sekolah dasar yangmemiliki lingkungan kurang baik (LKB) dengan dermatitis akut sebanyak 4 responden(11,7%) dan dermatitis kronik 19 responden (54,3%). diperoleh nilai yaitu p=0,00 yang lebihkecil dari Ã¡ = 0,005. Kesimpulan Dari hasil penelitian yang telah dilakukan di Desa TabangBarat Kecamatan Kecamatan Rainis Kabupaten Kepulauan Talaud, terdapat hubungan antarafaktor lingkungan dengan kejadian dermatitis pada anak usia sekolah. Saran diharapkanmenjadi sumbangan ilmiah dan informasi untuk peneliti selanjutnya tentang hubungan faktorlingkungan dengan kejadian dermatitis pada anak usia sekolah.Kata Kunci : Dermatitis, Faktor Lingkungan